BAGAIMANA PECKING-ORDER THEORY MENJELASKAN STRUKTUR PERMODALAN BANK DI INDONESIA? - suhardi, Suhardi; Afrizal, Afrizal (ECONOS Jurnal Ekonomi dan Sosial, 2019)
The pecking order theory of capital structure is one of the most influential theories of corporate finance. The purpose of this study is to explore the most important factors on a firm’s capital structure by pecking-order theory. Hierarchical regression is used as the analysis model. This study examines the determinants of debt decisions for 31Indonesianbanking companies that are quoted on the Indonesian Stock Exchange of 2010-2015. The results indicate that the determinants of capital structure are profitability and growth rate. The profitability negatively effects on the capital structure. It implies that firms prefer to use their earnings to finance business activities and thus useless debt capital. Growth rate positively affects capital structure. The greater growth opportunity will have more capital structure to finance the growth. Size is a moderator variable in this study. Size of firms moderates the effects of the tax rate on capital structure. Large firms appear to take advantage of the tax deductibility of debt. The findings are important for management and investors.